Navigating the Maze of Urban Voids: A Hybrid MCDM Approach for Site Selection for Urban Poor in PCMC, India - Harshad Raisoni; Tanaya Verma; Arati Petkar (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
The rapid pace of migration has incurred a higher demand and a lower supply ratio of economically weaker section (EWS) housing, prompting the emergence of illegal squatters across several Indian cities, especially on public reservation lands, turning them into urban voids. Numerous government initiatives, at the central, state, and urban local body levels, have been attempted to provide housing to the urban poor living in slums, predominantly through in-situ redevelopment. However, the efforts lagged for several reasons. One of the major reasons is the lack of a methodical process for the logical selection of available slum sites for rehabilitation or redevelopment. This creates a challenging situation for the decision makers to prioritize these sites, as currently it is based on the notification date of slums and is majorly driven by political will. Hence, this research attempted to formulate a prioritization model for the selection of slum sites in the PCMC area by evaluating them with parameters derived from expert opinion. The Hybrid Multiple Attribute Decision Making (MADM) model, using weights derived from Shannon’s entropy, and ranking performed using the TOPSIS method were considered for prioritization of the slum sites. This unbiased scientific process will guide the decision makers in the appropriate allocation of available resources to uplift the urban poor living in slums, which is crucial for the sustainable urban development of India.